The effect of a proposed training method using play exercises to develop specific agility and skill performance in football - Yasir Mohammed Hammood; Akram Hussein Rashid; Othman Adham Ali; Othman Ali (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The importance of research lies in preparing a proposed training curriculum that seeks to reach results believed to positively impact the development of football players' special agility and skill performance. Objective: The research aims to prepare a proposed training curriculum using play exercises and identify their impact on developing special agility and skill performance in football. Methodology: The researchers used the experimental method due to its suitability and the nature of the research. After the pre-tests were conducted, the proposed training curriculum was applied to the participants, and post-tests were conducted. Statistical means, including mean, standard deviation, and t-testing, were used to identify the effect of variables on participants' performance. Results: The results showed that there were statistically significant differences between the results of the pre-test and the post-test, as the value of the difference of the means was (5.75,3.81) and the difference of deviations of the averages (1.72,1.62), while the calculated t-value was (9.36,4.81), which are greater than the tabular T value of (2.04) with a level of significance (0.05) and a degree of freedom (15). Discussion: The researchers explain the development that occurred to the experimental group as a result of the use of play exercises in the training units and prepared scientifically, which affected the development of the level of performance, which helped to bring the players to the degree of mastery through its diversity and repetition during training. Conclusions: The researchers concluded that using play exercises within the training curriculum positively impacts the development of extraordinary agility and skill performance in football.